SCritics and dialogues in the light of therelation school versus external evaluations - Alves Araujo, Osmar Helio; Furtado Ribeiro, Luis Tavora; Santos Cruz, Jose Anderson [UNESP] (Univ Federal Sergipe, 2018)
This essay highlights that the external evaluations affect the autonomy of the schools and teachers in relation to the organization of the pedagogical work, even though the LDB assures the pedagogical autonomy regarding the organization of its practices based on its local needs and reality. In this sense, it is sought in this work to rely on studies and research that evidence the evaluation as against the regulation of the public school; Evaluation versus standardization / homogenization of contents and school curricula as a quality parameter; knowledge-regulation instead of knowledge-emancipation, as well as schools that associate rewards or punishment versus the results of external evaluations. Finally, it reiterates the need for managers, pedagogical coordinators and teachers to realize that it is necessary to strengthen their professional autonomy, the continued teacher training, the pedagogical organization of the school and, consequently, that this is reflected in the students' learning and, above all, in the (re) construction of the school.
Keywords: Critics and dialogue; School; External Evaluation; Pedagogical Aytonomy